Biosurfactants: Potential and Eco-Friendly Material for Sustainable Agriculture and Environmental Safety—A Review - Gayathiri, Ekambaram; Prakash, Palanisamy; Karmegam, Natchimuthu; Varjani, Sunita; Awasthi, Mukesh Kumar; Ravindran, Balasubramani (Agronomy (Basel), 2022)
With the present climate change and increasing world population, there is an urgent need to discover creative, efficient, and cost-effective natural products for the benefit of humanity. Biosurfactants are produced by various microorganisms that have several distinct properties compared to other synthetic surfactants, including mild production conditions, multifunctionality, higher biodegradability, and lower toxicity of living cells synthesis of active compounds. Due to their surface tension reducing, emulsion stabilizing, and biodegrading properties of these in place of chemical surfactants, they are generating huge demand in terms of research and usage. Biosurfactants are widely used in the food industry as food-formulation ingredients and antiadhesive agents as emulsifiers, de-emulsifiers, spreading agents, foaming agents, and detergents that find application in various fields such as agriculture, industrial sectors, and environmental recreation. Recent research focused more on heavy metal bioremediation from compost was achieved using biosurfactants-producing bacteria, which resulted in an improvement in compost quality. Although a number of studies on biosurfactants synthesis have been reported, very limited information on its cinematics and the consumption of renewable substrates are available. In this review paper, we made an attempt to critically review biosurfactants, their usage, research related to them, and challenges faced.